Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1001/jamanetworkopen.2022.31769
|View full text |Cite
|
Sign up to set email alerts
|

Association of Race and Ethnicity With Triage Emergency Severity Index Scores and Total Visit Work Relative Value Units for Emergency Department Patients

Abstract: Our study results suggest that significant racial and ethnic disparities exist in the ESI scores assigned to patients during nursing triage evaluation and in the intensity of services provided during physician evaluation for patients presenting with the same acute chief symptoms. When nurses assign White patients more acute ESI scores at triage, they may also order diagnostic tests prior to a physician's involvement, leading to downstream increases in wRVUs. Additional decisions made at triage associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 7 publications
(8 reference statements)
3
14
2
Order By: Relevance
“…In this multicenter cross-sectional study of patients presenting to the ED, we found that White patients with the same chief symptoms were frequently assigned more acute ESI scores compared with Black patients, Hispanic patients, and patients identifying as having an Other racial or ethnic background. These findings are broadly consistent with those of Joseph et al, 4 and the acute nature of these symptoms suggests that racial and ethnic disparities in triage cannot be explained primarily in terms of differences in visits for nonurgent care. 15 These disparities likely have structural, institutional, and interpersonal causes.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this multicenter cross-sectional study of patients presenting to the ED, we found that White patients with the same chief symptoms were frequently assigned more acute ESI scores compared with Black patients, Hispanic patients, and patients identifying as having an Other racial or ethnic background. These findings are broadly consistent with those of Joseph et al, 4 and the acute nature of these symptoms suggests that racial and ethnic disparities in triage cannot be explained primarily in terms of differences in visits for nonurgent care. 15 These disparities likely have structural, institutional, and interpersonal causes.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings differ from previous studies considering the total number of wRVUs associated with patients' ED visits, as we did not find a higher visit intensity for White patients. 4 Instead, we found that patients with Black, Hispanic, and Other racial and ethnic backgrounds tended to have higher wRVUs associated with their visits for many symptoms. As White patients in our study tended to be older and might be expected to have higher visit acuity, these findings suggest that the racial and ethnic disparities observed in triage may be more consequential than they might initially appear.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…However, the tool is a subjective measure applied with wide variability which introduces opportunity for bias . For example, minoritized racial and ethnic groups who do not receive immediate care wait longer to be seen and Black patients are assigned lower triage scores and experience longer wait times, which can result in increased leaving without being seen (LWBS) rates . Furthermore, LWBS has been associated with ED revisit rates which is increasingly used as an ED and hospital performance measure .…”
Section: Introductionmentioning
confidence: 99%